Development of Open Education Resources to Teach Oral History: Perspectives of a Sports Heritage-Engaged Scholarship Initiative in Gauteng, South Africa - Schellnack-Kelly, Isabel; Saurombe, Nampombe P (Mousaion: South African Journal of Information Studies, 2024)
Gaps exist in archival practices, and developments are in progress to decolonise and transform archives by supplementing existing archival collections with oral history accounts. This is a recent development in the archival field, requiring archivists and records managers to become aware of how oral history collections should be undertaken to preserve testimonies related to socio-economic, sociopolitical, and cultural events not yet captured by South African public archivists. An open educational resource (OER) was developed in 2022 as part of an engaged scholarship initiative to instruct archivists on oral history research techniques and how to apply research ethics when undertaking such projects. The research paradigm for this study was a postmodernist qualitative study. Action-based research was used in the research design. Action research is a flexible methodology uniquely suited to research and support change. It integrates social research with exploratory actions to promote development. Action research outcomes are both practical and theoretical. The knowledge it generates directly and continuously impacts the changing practices of the participants. Data from participants were collected through recorded project workshops and meetings. The content for the OER was developed from observing online videos showcasing oral history interviews, consulting literature on OER development, and discussions with archivists and heritage collectors at the South African National Film, Video and Sound Archives, the South African National Parks Board, and the Gauteng Provincial Archives. The OER was developed to enable collaboration to ensure that the oral narratives of postcolonial Africa, particularly post-apartheid South Africa, are not lost but captured by the public archives’ services for the benefit of South Africans and other interested stakeholders.